Niche Modelling: a comparison between modelling methods best applied for Cnidaria niche dispersion studies - Lima, Alessandra Vallim [UNESP] (2017)
Recently, ecological niche modelling has been receiving more attention in several areas in biology, due to the evolution of personal computers, and the increasing availability of data used in modelling. The results obtained can be used in preventive actions such as species management and invasive species distribution. Since its increasing popularity, several algorithms are available and undergoing tests regarding their performance towards different phylum. Marine invertebrates, more specifically cnidarians, present few studies on this field, and should receive closer attention in the next years due to worldwide increases in jellyfish population (blooms), and bleaching in almost every known shallow water coral reef. Because of this gap of information, we chose this still poor studied group to compare three algorithms. We used MAXENT, GARP and AquaMaps in its desktop form and selected them based on other studies comparing algorithms. Our aim was to, based on different organisms of the phylum Cnidaria, Lychnorhiza lucerna, Chrysaora lactea, Phyllorhiza punctata, Tamoya haplonema, Ceriantheomorphe brasiliensis and Mussismilia hispida, compare those algorithms and examine which one performed the best. Our results shown that MAXENT outperformed the other algorithms both regarding de Area Under the ROC Curve (AUC) and the map distribution. GARP show varying results with generalized maps and AquaMaps was the least accurate of them. Our results are similar to those found in other papers, thus meaning that MAXENT is the most reliable software when it comes to modelling these animals.